Poly(4-Vinylpyridinium)Hydrogen Sulfate Catalyzed an Efficient and Ecofriendly Protocol for the One-Pot Multicomponent Synthesis of 1,8-Acridinediones in Aqueous Medium - Janardhan Banothu; Rajitha Bavantula; Peter A. Crooks (Journal of Chemistry)
Highly efficient, ecofriendly, and improved protocol for the synthesis of 1,8-acridinediones has been developed via one-pot multicomponent condensation of 1,3-cyclohexanedione/dimedone, aromatic aldehydes, and ammonium acetate utilizing poly(4-vinylpyridinium)hydrogen sulfate as catalyst in aqueous medium. Excellent yields in shorter reaction time, simple work-up procedure, easy recovery, and reusability of the catalyst are attractive features of this green protocol.